Surfactantless emulsions containing eugenol for imidacloprid solubilization: Physicochemical characterization and toxicity against insecticide-resistant cimex lectularius - Cáceres, Mariano (2020)
Synthetic insecticides have been used for a long time as one of the most effective tools for insect pest control. However, the re-emergence of insect pests and their fast development of resistance, as has occurred for pyrethroid-resistant bed bugs Cimex lectularius L., make it necessary to develop new and safe strategies for effective pest control. This has fostered the research on new eco-sustainable formulations based on essential oils, which allows reducing the impact associated with the intensive use of synthetic insecticides on the environment and their effects on human health. This research explores the stability of water/eugenol/ethanol surfactantless emulsions loaded with imidacloprid (0.003 wt%), and their toxicity against a resistant bed bug strain. The results have shown that these emulsions enable the solubilization of a poorly water-soluble drug, such as the imidacloprid, without any significant modification of their stability. Furthermore, the application of the obtained formulations against the pyrethroid-resistant bed bug results in mortality in the 50–85% range upon topical and spray applications, with the increase of the eugenol content enhancing the effectiveness of the formulations. It may be expected that the ternary water/eugenol/ethanol mixtures could be further developed in the preparation of ready to use formulations, enabling the dispersion of insecticides for pest control.